PEMBENTUKAN DAN PENGUATAN KELOMPOK SIAGA BENCANA (KSB) SEBAGAI WUJUD KESIAPSIAGAAN MASYARAKAT TERHADAP BANJIR DI KANAL BANJIR BARAT KOTA SEMARANG - Wiwandari Handayani; Reny Yesiana; Mega Anggraini (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2018)
Flood management became one of the development priorities in Semarang since it leading to massive loss and damage to life and assets. The flood disaster in Kaligarang that occurred in 1990, has been the driving force to anticipate the flood risk in the West Flood Canal. Semarang City Government has made efforts to minimize the risk of flooding through the construction of Jatibarang reservoir. However, with the current conditions, such as increased rainfall intensity and reduced upstream catchment function, the risk of flooding in areas of West Flood Canal is also increasing, so communities preparedness is absolutely necessary. As part of supporting the government of Semarang City, Mercy Corps Indonesia in collaboration with the Initiative for Urban Climate Change and Environment (IUCCE) and the Initiative for Regional Development and Environmental Management (IRDEM) with support funding from Z Zurich Foundation to help community in sub-districts along Semarang West Flood Canal to have proper planning in dealing with flood risk. One of community preparedness form is to establish a disaster preparedness group (kelompok siaga bencana-KSB) which functions to organize communities when facing disasters. The purpose of this article is to examine the process and benefits of the KSB establishment for the community and local government (sub-district), and its become lesson learned for other regions. The research method is qualitative, with primary data collection techniques is semi-open interviews. Sampling technic used in this interview was purposive sampling, because respondent was chosen by their competency. Besides, observations were done on each activities and literature review. The results of this study are the process of implementing the establishment and strengthening of the KSB and increasing the benefits of KSB about 37% because the community has received disaster preparedness training.